Role of Biochar in Anaerobic Digestion Based Biorefinery for Food Waste - Wambugu, Carol W.; Rene, Eldon R.; van de Vossenberg, Jack; Dupont, Capucine; van Hullebusch, Eric D. (Frontiers in Energy Research, 2019)
The effect of biochar addition on the anaerobic digestion (AD) of food waste was evaluated. From the five biochars tested, Fe, Co, Ni, and Mn were leached in very small quantities (<10 mg/kg), while a high amount of K (1,510 and 1,969 mg/kg) was leached from treated waste wood and willow tree pyrochar, respectively. AD batch experiments were performed at an inoculum:substrate ratio of 1:1, at 30°C and under agitating conditions. The results showed that the biogas volume produced by the treatments with the brewery residue hydrochar and treated waste wood pyrochar was lower than the amount of biogas produced by the control with only food waste. The food waste supplemented with 1.5 mL of trace elements yielded the highest biogas of 588 mL/g COD (CH4 content−48%). Furthermore, two identical upflow anaerobic sludge blanket (UASB) reactors, i.e., control reactor and biochar amended reactor, were operated at 30°C, at organic loading rates (OLR) varying from 3.4 to 7.8 g COD/L.day. The average COD removal efficiencies of the control and the biochar-amended reactor were 47 and 77% at an OLR of 6.9–7.8 g COD/L.day, respectively. These study results clearly indicate that the type of biochar and trace elements concentration in biochar play a key role in determining the effectiveness of the biochar in enhancing biogas production from food waste.